Calpain 2 regulates IL-1α secretion and inhibits tumor development via modulating calpain 1 expression in the tumor microenvironment - Zuhairah Binte Hanafi; Yu Mei; Huey Yee Teo; Ying Zhu; Chew Chin Yong Lionel; Jing Wen Chiu; Jinhua Lu; Haiyan Liu (OncoImmunology)
Tumor-promoting inflammation significantly impacts cancer progression, and targeting inflammatory cytokines has emerged as a promising therapeutic approach in clinical trials. Interleukin (IL)-1α, a member of the IL-1 cytokine family, plays a crucial role in both inflammation and carcinogenesis. How IL-1α is secreted in the tumor microenvironment has been poorly understood, and we previously showed that calpain 1 cleaves pro-IL-1α for mature IL-1α secretion, which exacerbates hepatocellular carcinoma by recruiting myeloid-derived suppressor cells. In this study, we report that calpain 2 also modulates IL-1α secretion. Notably, a deficiency in calpain 2 resulted in enhanced hepatocellular carcinoma development within an IL-1α-enriched tumor microenvironment. Further investigations revealed that calpain 2 deficiency increased calpain 1 expression, implying a compensatory mechanism between the two calpains. Mechanistically, calpain 2 deficiency led to increased expression of FoxO3, which is a forkhead transcription factor that promotes calpain 1 expression. Collectively, these results suggest that calpain 2 modulates calpain 1 expression, and therefore IL-1α secretion through the induction of FoxO3, offering novel potential therapeutic targets for cancer treatment.